2020
DOI: 10.2147/opth.s274281
|View full text |Cite
|
Sign up to set email alerts
|

<p>iStent Trabecular Micro-Bypass Stent Implantation with Cataract Surgery in a Japanese Glaucoma Population</p>

Abstract: Introduction: This study assesses two-year efficacy and safety following implantation of a single trabecular micro-bypass stent (iStent ®) with concomitant phacoemulsification cataract surgery in Japanese patients with open-angle glaucoma (OAG). Materials and Methods: This retrospective, consecutive case series included eyes that underwent iStent implantation with phacoemulsification and were followed for 24 months postoperative. Efficacy and safety measures included intraocular pressure (IOP), number of glauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 60 publications
4
14
0
Order By: Relevance
“…A substantial number of studies have demonstrated significant long-term IOP reduction and medication reduction following the implantation of the iStent. [11][12][13][14][15][16] Our previous study 13 was focused on physiology of aqueous outflow and was intended to confirm the conclusions of work of Batista et al 17 Current manuscript is a typical clinic research, and similar to recent population studies [18][19][20] its aim is to confirm the results of iStent implantation combined with a cataract surgery taking into consideration a Caucasian Polish population.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…A substantial number of studies have demonstrated significant long-term IOP reduction and medication reduction following the implantation of the iStent. [11][12][13][14][15][16] Our previous study 13 was focused on physiology of aqueous outflow and was intended to confirm the conclusions of work of Batista et al 17 Current manuscript is a typical clinic research, and similar to recent population studies [18][19][20] its aim is to confirm the results of iStent implantation combined with a cataract surgery taking into consideration a Caucasian Polish population.…”
Section: Introductionmentioning
confidence: 76%
“…The mean age of the population at the time of surgery was 73.7 ± 4.5 years. Another study evaluating the iStent effectiveness on the Asian population was the one conducted by Nitta et al 20 carried on a Japanese glaucoma population, which has a significantly greater incidence of NTG than most other populations. They enrolled 74 patients with a mean age of 73 years for implantation of the iStent combined with phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…With up to 7 years of postoperative follow-up, iStent studies have often focused on patients with mild to moderate POAG undergoing cataract surgery, but an increasing number of studies have assessed iStent for different glaucoma types (eg, pseudoexfoliative, angle-closure, pigmentary), more advanced severity, standalone cases, and in combination with other procedures or stents. [11][12][13][14][15][16][17][18][19][20][21][22][23] The more recent iStent inject ® Trabecular Micro-Bypass (CE Mark 2010, FDA approval 2018) contains two stents that create two patent bypasses through the diseased trabecular meshwork. This device has been studied both with and without concomitant cataract extraction, and in studies with up to 5 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Another retrospective study involving 64 eyes observed a 7.2% CEC loss over 12 months [26]. The longest retrospective study to date of 53 eyes also reported a CEC loss of 3.6% over 24 months in a Japanese population [27]. In another study, no significant CEC loss was noted 6 months after two iStent devices were implanted in 10 eyes [28].…”
Section: Istent and Istent Injectmentioning
confidence: 95%